Efektivitas Model Pembelajaran Student Team Achievement Division (STAD) dalam Mengidentifikasi Informasi dan Meringkas Teks Eksplanasi pada Siswa Kelas VIII SMP Muhammadiyah 10 Makassar (International Forum of Researchers and Lecturers, 2023)
This research is an experimental research with pre-experiment method, this research design is the one group pretest posttest. This study aims to determine the effectiveness of the Student Team Achievement Division (STAD) learning model in identifying information and summarizing explanatory text. The samples in this study were VIII grade students. Based on the results of research and data analysis regarding the comparison of statistical values, the comparison of learning outcomes categories and the comparison of the level of completeness proves that the improvement of student learning outcomes can be seen from the data on student learning outcomes through descriptive statistical analysis before using the Student Team Achievement Division (STAD) learning model, the average student score is still below the KKM value, namely 49.57 and after using the Student Team Achievement Division (STAD) learning model, the average student score increases above the KKM, namely 84.21. It is known that the posttest value is 84.21 more than the Pretest value which is 49.57. Furthermore, based on the results of inferential statistical analysis using the t-test formula, it is known that the t_ (count) obtained is 4.371 with the frequency df = 14 -1 = 13, at a significant level of 0.05 or 5% the t_table is 1.770. So t_ (count) > t_table or H_0 rejected H_1 accepted. These results can be concluded that there is a significant increase in student learning outcomes. This means that the use of the Student Teams Achievement Division (STAD) learning model is effective in learning to identify information and summarize explanatory texts in class VIII students of SMP Muhammadiyah 10 Makassar.